Specific combined actions in Turia river during 2005-2007 drought - Ferrer J.; Pérez M.A.; Perez F.; Artés J.B. (Drought management: scientific and technological innovations, 2008)
The last extreme drought that affects the Júcar River Basin Authority, occurs during 2005-2007 and it expands to the Turia river too. This is an important hazard to the Turia river environment, Valencia urban supply and traditional irrigation areas of this system. A combination of different measures, from the Jucar River Basin Authority, starts during year 2005, such as important water saving in irrigation areas, with the establishment of irrigation turns, an important urban wastewater reuse in irrigation areas, by Local and Regional Government, the possibility of drought wells use, by the users, and the follow-up of the river flows and channel flows for irrigation. The start of this set of drought management measures needs important co-ordinated efforts with the different administrations involved and users, with the objective of minimizing the environmental, economic and social impact of the drought. More than 40 cubic hectometres have been used in environmental or agricultural uses during the last year, and it has been possible reduce in less than fifty percent the regulation reservoirs outflows, that supposes and important guarantee for this and future years to keep the environmental flows maintenance and urban supply. In this paper the set of measures established during this drought in the Turia system is detailed.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)